Market Volatility As a Financial Soundness Indicator : An Application to Israel - Mendez Morales, Armando (IMF Working Papers; Working Paper, 2003)
Financial decisions of economic agents are based on volatility considerations. However, no aggregate indicators have been used by policymakers and regulators to assess the market risk environment. This paper applies a market volatility indicator to analyze the Israeli's transition toward inflation targeting. Unlike conventional measures of volatility, it shows a substantial decline once volatility is measured against the minimum variance for the same returns on assets. Using a conventional Multivariate GARCH model, we find that interest rates sensitivity to changes in the risk environment may be important for a correct identification of volatility patterns of individual assets.